Relationships between native small mammals and native and introduced large herbivores. (3rd July 2013) - Pedersen, Simen; Andreassen, Harry P.; Keith, David A.; Skarpe, Christina; Dickman, Christopher R.; Gordon, Iain J.; Crowther, Mathew S.; McArthur, Clare
Abstract Australia has a range of native and introduced large herbivores that could affect the abundance of small mammals through direct and indirect effects. Here we study the relationship between occurrence of the introduced rusa deer (Rusa timorensis) and the native swamp wallaby (Wallabia bicolor), and the abundance of four species of native small mammals in coastal heath vegetation with varying fire history. The abundance of two species, the brown antechinus (Antechinus stuartii) and bush rat (Rattus fuscipes), was related to occurrence of large herbivores and was dependent also on fire history. Abundance of swamp rats (R. lutreolus) and New Holland mice (Pseudomys novaehollandiae) was not related to the occurrence of any of the large herbivores, and did not depend on fire history. At sites burned within the last 9 years, captures of brown antechinus were negatively related to both deer and wallaby occurrence, and captures of bush rats were negatively related to deer occurrence. However, at sites that burned more than 15 years ago, captures of brown antechinus and bush rats were not related to large herbivore occurrence. Overall there was either no relationship, or a negative one, between small mammals and the large herbivores. This mensurative study has demonstrated relationships between deer and wallabies and small mammals, with fire as an additional important factor. From the results of the current study we put forward a series of hypotheses that need to be tested by future experiments.